Analysis the Influence of Principal Leadership Style, Facilities, and Work Discipline on Teacher Performance with Motivation as Intervening Variable - Andriansyah, Agussalim; Wiyarni, Wiyarni; Novalina, Riska (International Journal of Scientific Research and Management (IJSRM), 2023)
School is an official educational institution whose job is to organize the process of education and learning. School management issues are mainly related to the importance of the effectiveness and efficiency of education delivery. Performance is a measure of the success of a person or institution in running a management system. However, in this case, the reality is that the teacher's performance is often not in line with expectations. This study uses teacher performance (Y) as the dependent variable with leadership style (X1), school facilities (X2), discipline (X3) as the independent variable and work motivation (Z) as the intervening variable. The research method used is a quantitative method, using multiple linear regression formulas. The sample in this study was 235 junior high school teachers in the Pondok Aren sub-district, South Tangerang. By using a questionnaire as a research instrument with a rating score using a Likert scale. The tests used in this study are validity and reliability tests, classical assumption tests, and path analysis. The results of the data show that all items in the questionnaire are declared valid and reliable. For the classic assumption test, no problems were found. For path analysis, it was found that the contribution of the principal's leadership style, school facilities, and work discipline and work motivation to teacher performance was 45.5%, while the remaining 54.5% was contributed by the variables not examined. Indirectly the variables of school facilities and work discipline through work motivation have a significant effect on teacher performance. However, motivation cannot be an intervening variable between the principal's leadership style (X1) and teacher performance (Y) because the value of the direct effect of X1 on Y is 24.2% greater than the indirect effect of X1 on Y, which is 16.8%. Key words: Principal Leadership Style, School Facilities, Discipline, Work Performance, and Work Motivation